Profile of patients in private home care who developed ventilator-associated pneumonia - Fabiana Schimidt Cezar; Fabiana Camolesi Jacober; Heloísa Amaral Gaspar Gonçalves; Katia Vanessa Cantarini; Claudio Flauzino de Oliveira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to analyze the profile and clinical outcomes of patients who developed Ventilator-Associated Pneumonia (VAP) in private home care and to compare the incidence with national data. Methods: this was a retrospective study with data collected from July 2021 to June 2022 from patient records at a private clinic. Patients using intermittent ventilation or without ventilatory support were excluded. Results: the utilization rate of mechanical ventilation was 15.9%. The incidence density of pneumonia in pediatrics was 2.2 cases per 1000 ventilation-days and in adults was 1.7 cases per 1000 ventilation-days, figures lower than those reported by the National Health Surveillance Agency. There were 101 episodes of pneumonia in 73 patients, predominantly male (65.8%), adults (53.4%), and those with neurological diseases (57.5%). The treatment regimen predominantly took place at home (80.2%), and there was one death. Conclusions: patients in home care showed a low incidence and mortality rate from ventilator-associated pneumonia.